2011
DOI: 10.1186/1475-2875-10-248
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers of antifolate resistance in Plasmodium falciparum isolates from Luanda, Angola

Abstract: BackgroundPlasmodium falciparum malaria remains a leading health problem in Africa and its control is seriously challenged by drug resistance. Although resistance to the sulphadoxine-pyrimethamine (SP) is widespread, this combination remains an important component of malaria control programmes as intermittent preventive therapy (IPT) for pregnant women and children. In Angola, resistance patterns have been poorly characterized, and IPT has been employed for pregnant women since 2006. The aim of this study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
4
8
0
Order By: Relevance
“…Double-or triple-mutant haplotypes were the most common for the pfdhfr gene, especially I 51 R 59 N 108 and I 51 N 108 . pfdhfr 51I was the second most prevalent, similar to the previous studies in Angola (40)(41)(42)(43). pfdhfr 164L was only found in one isolate and presented in association with I 51 R 59 N 108 , which was rare in Africa and could be detected occasionally together with 108N ϩ 51I and/or 59R (44).…”
Section: Discussionsupporting
confidence: 87%
“…Double-or triple-mutant haplotypes were the most common for the pfdhfr gene, especially I 51 R 59 N 108 and I 51 N 108 . pfdhfr 51I was the second most prevalent, similar to the previous studies in Angola (40)(41)(42)(43). pfdhfr 164L was only found in one isolate and presented in association with I 51 R 59 N 108 , which was rare in Africa and could be detected occasionally together with 108N ϩ 51I and/or 59R (44).…”
Section: Discussionsupporting
confidence: 87%
“…Overall, in that study, 25% of the isolates collected from different localities in the country presented the triple pfdhfr mutant alleles. In another study on isolates collected in Luanda [ 25 ], 31 of 61 (51%) samples were triple pfdhfr mutants, and 25 of 61 (41%) and 4 of 61 (6.6%) isolates were Ile-51/Asn-108 and Arg-59/Asn-108 double mutants, respectively. In the northern province of Uige, the majority (40 of 66, 61%) of clinical isolates were double Ile-51/Asn-108 pfdhfr mutants, followed by triple mutants (23 of 66, 35%) and the alternative double Arg-59/Asn-108 mutant (n = 1) and wild-type (n = 2) [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in Luanda, SGKAA was also the most frequent haplotype (18 of 30, 60%), followed by AGKAA (7 of 30, 23%) and the wild-type SAKAA (2 of 30, 7%) [ 25 ]. SGEAA and SGEGA haplotypes were found in 3 isolates in that study.…”
Section: Resultsmentioning
confidence: 99%
“…A study in Cameroon reported that codon 108 (S108N) has increased inexorably from 48% in 1994-1995, 71% in 1997-1998, and 93% in 2000 -2001. 32 The triple mutations, S108N, N51I, and C59R were evident in 100%, 93%, and 57% of isolates, respectively, in recent surveys in Angola 33 and in Tanzania, 100%, 100%, 100%, and 100% of isolates for 59R, 108N, 436S/437G, and 540E, respectively, in 2007 from a low transmission area. 34 Data from Uganda also showed within 99%, near 99%, and 57-94% of isolates respectively for the 108, 51, and 59 mutations.…”
Section: Discussionmentioning
confidence: 99%